Seeking cervical cancer information from interpersonal sources among Malaysian women in Selangor - Soo, Shey San; Ahmad, Abdul Mua'ti @ Zamri; Hasan, Hamisah; Shamshudeen, Rosya Izyanie; Mazlan, Azriaty (American-Eurasian Network for Scientific Information, 2015)
Background: Cervical cancer is the second most common cancer among women in Malaysia after breast cancer. Previous studies have focused on the association between information disclosure about cervical cancer through the mass media and intention to undergo Pap Smear tests, but its remain unclear whether or not women use interpersonal communication to seek cervical cancer information. Objective: This study explores the information seeking behaviour using interpersonal sources among women who underwent a Pap Smear test in Klang valley. Results: The level of trust in interpersonal sources is higher than the usage level of interpersonal sources to seek cervical cancer information. Conclusion: Having a better understanding of cervical cancer information seeking behaviour through interpersonal communication will facilitate information intervention for women in Malaysia, especially in Selangor.